2015
DOI: 10.1093/toxsci/kfv136
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Characterization of 4 Human Liver-Derived Single Cell Culture Models Reveals Significant Variation in the Capacity for Drug Disposition, Bioactivation, and Detoxication

Abstract: In vitro preclinical models for the assessment of drug-induced liver injury (DILI) are usually based on cryopreserved primary human hepatocytes (cPHH) or human hepatic tumor-derived cell lines; however, it is unclear how well such cell models reflect the normal function of liver cells. The physiological, pharmacological, and toxicological phenotyping of available cell-based systems is necessary in order to decide the testing purpose for which they are fit. We have therefore undertaken a global proteomic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 39 publications
(39 reference statements)
1
67
0
2
Order By: Relevance
“…Though these cell lines are wellestablished, cheap, easy to handle, and allow generation of reproducible data in a highthroughput setting, they are limited by their immature phenotypes. CYP activities and expression of DMEs and hepatic transporters are drastically lower in these cell lines compared to primary human hepatocytes (PHH) (198)(199)(200), which is also reflected in their reduced sensitivity towards drug hepatotoxicity compared to PHH and the lack of CYP inducibility in the case of HepG2 cells (200,201). To overcome the limited liver-specific functionalities, cell lines overexpressing specific DMEs or NRs have been established for improved toxicity prediction and assessments of CYP enzyme induction (202)(203)(204), yet the overall molecular phenotypes still remain drastically different from the human liver in vivo.…”
Section: Conventional In Vitro Modelsmentioning
confidence: 99%
“…Though these cell lines are wellestablished, cheap, easy to handle, and allow generation of reproducible data in a highthroughput setting, they are limited by their immature phenotypes. CYP activities and expression of DMEs and hepatic transporters are drastically lower in these cell lines compared to primary human hepatocytes (PHH) (198)(199)(200), which is also reflected in their reduced sensitivity towards drug hepatotoxicity compared to PHH and the lack of CYP inducibility in the case of HepG2 cells (200,201). To overcome the limited liver-specific functionalities, cell lines overexpressing specific DMEs or NRs have been established for improved toxicity prediction and assessments of CYP enzyme induction (202)(203)(204), yet the overall molecular phenotypes still remain drastically different from the human liver in vivo.…”
Section: Conventional In Vitro Modelsmentioning
confidence: 99%
“…Primary human hepatocytes retain their metabolic capacity in suspension for some hours, but when plated, the expression of drug‐metabolizing enzymes and drug uptake transporters will be reduced to very low levels . Recently, a large multi‐centre study compared the toxicity using a set of nine liver‐toxic drugs and four compounds not associated with any liver toxicity in HepG2, HepaRG and Upcyte cells in conventional 2D cultures . It was concluded that none of the cell models could distinguish between liver‐toxic and non‐liver‐toxic compounds and thus not useful to investigate new chemical entities.…”
Section: In Vitro Models To Study Drug Metabolism and Drug‐induced LImentioning
confidence: 99%
“…Several publications have recently appeared in which the here selected training compounds and negative controls have been investigated in order to substantiate their utility as training compounds to profile and elucidate further DILI mechanisms and to interrogate existing and novel in vitro systems for the prediction of human DILI (Sison-Young et al 2015; Bell et al 2016; Sison-Young et al 2016; den Braver-Sewradj et al 2016; den Braver et al 2016). …”
Section: Discussionmentioning
confidence: 99%